High-fat diet–induced plasma protein and liver changes in obese rats can be attenuated by melatonin supplementation - Prapimpun Wongchitrat (2018)
© 2017 Elsevier Inc. Obesity triggers changes in protein expression in various organs that might participate in the pathogenesis of obesity. Melatonin has been reported to prevent or attenuate such pathological protein changes in several chronic diseases. However, such melatonin effects on plasma proteins have not yet been studied in an obesity model. Using a proteomic approach, we investigated the effect of melatonin on plasma protein profiles after rats were fed a high-fat diet (HFD) to induce obesity. We hypothesized that melatonin would attenuate abnormal protein expression in obese rats. After 10 weeks of the HFD, animals displayed increased body weight and fat accumulation as well as increased glucose levels, indicating an obesity-induced prediabetes mellitus–like state. Two-dimensional gel electrophoresis and liquid chromatography–mass spectrometry/mass spectrometry revealed 12 proteins whose expression was altered in response to the HFD and the melatonin treatment. The altered proteins are related to the development of liver pathology, such as cirrhosis (α1-antiproteinase), thrombosis (fibrinogen, plasminogen), and inflammation (mannose-binding protein A, complement C4, complement factor B), contributing to liver steatosis or hepatic cell death. Melatonin treatment most probably reduced the severity of the HFD-induced obesity by reducing the amplitude of HFD-induced plasma protein changes. In conclusion, we identified several potential biomarkers associated with the progression of obesity and its complications, such as liver damage. Furthermore, our findings reveal melatonin's beneficial effect of attenuating plasma protein changes and liver pathogenesis in obese rats.